Metabolomic Analysis in Inflammatory Bowel Disease: A Systematic Review. (11th November 2020) - Gallagher, Kate; Catesson, Alexandra; Griffin, Julian L; Holmes, Elaine; Williams, Horace R T
Abstract: Background and Aims: The inflammatory bowel diseases [IBD], Crohn's disease and ulcerative colitis, are chronic, idiopathic gastrointestinal diseases. Although their precise aetiology is unknown, it is thought to involve a complex interaction between genetic predisposition and an abnormal host immune response to environmental exposures, probably microbial. Microbial dysbiosis has frequently been documented in IBD. Metabolomics [the study of small molecular intermediates and end products of metabolism in biological samples] provides a unique opportunity to characterize disease-associated metabolic changes and may be of particular use in quantifying gut microbial metabolism. Numerous metabolomic studies have been undertaken in IBD populations, identifying consistent alterations in a range of molecules across several biological matrices. This systematic review aims to summarize these findings. Methods: A comprehensive, systematic search was carried out using Medline and Embase. All studies were reviewed by two authors independently using predefined exclusion criteria. Sixty-four relevant papers were assessed for quality and included in the review. Results: Consistent metabolic perturbations were identified, including increases in levels of branched chain amino acids and lipid classes across stool, serum, plasma and tissue biopsy samples, and reduced levels of microbially modified metabolites in both urine [such as hippurate] and stool [such as secondary bile acids] samples. Conclusions: This review provides a summary of metabolomic research in IBD to date, highlighting underlying themes of perturbed gut microbial metabolism and mammalian–microbial co-metabolism associated with disease status.